Effectivity of Management Events with Integrated System Organization Rumah Sakit Dr. Oen Kandang Sapi Solo - Komala Dewi, Laurentina Karissa (Rumah Sakit Akademik Universitas Gadjah Mada, 2022)
Background: To provide information on health services and education, hospitals require marketing communication, one of which is event. The hospital holds a variety of events for employees and citizen, which are routine or even incidental. Along with era development, hospitals are required to make fast and precise movements, so that performance is efficient and effective to achieve the success of events. President Director of RUMAH SAKIT Dr. OEN KANDANG SAPI SOLO (Droenska) decided to establish the Hospital Event Committee in 2019 with integrated system organization (ISO DOI) to replace the role of the event committee which is formed in every events. It is expected that the performance of each unit can be more effective, efficient, and the entire hospital community makes the culture of hospitals, internal marketers, as a way of life, because intangible marketing assets are important to embrace customers. After the Decision of the President Director is determined and implemented, of course, monitoring and evaluation are required.Purpose: Evaluating the effectiveness of events management which used Integrated System Organization RUMAH SAKIT Dr. OEN KANDANG SAPI SOLO (ISO DOI).Method: Qualitative descriptive research was used. The research datas were obtained through in-depth interviews with 17 informans who are choosen by purposive sampling selection method at the Hospital Event Committee in 2019–2020. Then it is formulated with the study of proposal recapitulation data as well as liability sheet (LPJ) in 2019–2020.Result: Component and function of Hospital events committee already fulfilled the standard of EO. The concept of events is quite good and clear. Coordination between the committees of events is inadequate due to a lack of communication and initiative. The event went smoothly and also there were no obstacles that led to the failure of the event, although there were still some shortcomings. Some of the event committees have not evaluated and given accountability (LPJ).Conclusion: The completeness of EO component’s and work function’s already exists and running on the Hospital Event Committee (ISO DOI). Events held by hospital with ISO DOI committees become more organized, effective, and efficient, but the function of coordination and evaluation must be improved. ISO DOI is potensial to develop as an event organizer that manage events with partners so that it can be additional revenue for Droenska.